2021
DOI: 10.1145/3479856
|View full text |Cite
|
Sign up to set email alerts
|

Putting Tools in Their Place: The Role of Time and Perspective in Human-AI Collaboration for Qualitative Analysis

Abstract: Large datasets or 'big data' corpora are typically the domain of quantitative scholars, who work with computational tools to derive numerical and descriptive insights. However, recent work asks how computational tools and other technologies, such as AI, can support qualitative scholars in developing deep and complex insights from large amounts of data. Addressing this question, Jiang et al. found that qualitative scholars are generally opposed to incorporating AI in their practices of data analysis. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…IE and data labeling are used in a variety of settings, each with a distinct set of challenges. Not all settings are similarly suitable for human-computer collaboration (Jiang et al, 2021), and practitioners often resist solutions which over focus on automation instead of providing assistance (Feuston and Brubaker, 2021). To ground our investigation of human-computer collaboration in IE, we start by exploring two use cases related to the criminal justice domain (Section 2.1).…”
Section: Requirements Of High-precision Information Extractionmentioning
confidence: 99%
“…IE and data labeling are used in a variety of settings, each with a distinct set of challenges. Not all settings are similarly suitable for human-computer collaboration (Jiang et al, 2021), and practitioners often resist solutions which over focus on automation instead of providing assistance (Feuston and Brubaker, 2021). To ground our investigation of human-computer collaboration in IE, we start by exploring two use cases related to the criminal justice domain (Section 2.1).…”
Section: Requirements Of High-precision Information Extractionmentioning
confidence: 99%
“…They found that, when co-creating with AI, creators were concerned about ownership, leadership, AI feedback and evaluation, accountability, data collection and usage, personified communicative AI, and AI access to public data. In the field of human-AI collaboration, researchers have studied creators' perceptions and practices about the complementary of AI and humans [16,42]. Lubars and Tan [46] argued that designers need to consider what AI should do rather than what it can do.…”
Section: 22mentioning
confidence: 99%
“…At the same time, there has been extensive work from the HCI community on how qualitative coders would like automation to assist them during the coding process (Marathe and Toyama, 2018;Feuston and Brubaker, 2021;Chen et al, 2018;Haug et al, 2021). These studies show that while researchers desire automation, they believe the coding agency should remain in their hands.…”
Section: Related Workmentioning
confidence: 99%